EXAMINING ENTERPRISE RISKMANAGEMENT IMPLEMENTATION AND FIRM PERFORMANCE THROUGH ECONOMIC VALUE ADDED ANALYSIS - SHAD, MUHAMMAD KASHIF (2015)
Of late, there has been a rising emphasis on Enterprise Risk Management (ERM) in businesses globally. The primary objective of this study is to examine the impact of ERM implementation on corporate performance by introducing a superior value based measurement technique namely, Economic Value Added (EVA). EVA has been widely used in developed countries such as the USA, Australia, and New Zealand etc. however, developing countries, including Malaysia, are still lagging behind in using EVA for performance measurement purposes. Nevertheless, EVA is argued to be a superior performance measurement tool because it incorporates mutual cost of equity and cost of debt. The second objective of this study is to validate a creation transmission mechanism ofERM implementation.